Pengaruh Pembelajaran Mini Riset Berbasis Kearifan Lokal terhadap Penguasaan Materi dan Analisis permasalahan Konservasi Lingkungan - Asrorul Azizi, Muh. Zaini Hasanul Muttaqin (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2021)
This study aims to determine the impact of Mini Learning Research Based on Local Wisdom on Material Mastery and Analysis of Environmental Conservation problems with the theme of the diversity of living things. Mastery of the concept of conservation biology is very important in its application in real life to change students' attitudes, skills, values, behavior, and beliefs towards nature, which in turn can trigger sustainable development. The method used in this study is a quasi-experimental design with a nonequivalent control group design. The results showed that the mastery of concepts after the application of mini research learning based on local wisdom (post-test) was higher (80) than the control class (66). Moreover, the ability to master content (N-gain) after the mini application of research learning based on local wisdom was 0.69, higher than the control class (0.47). Furthermore, the results of the t-test showed that there were differences in students' content mastery between the experimental and control classes. That is, mini research learning based on local wisdom has an impact on content mastery